Human Resource Development in Improving Lecturer Performance - Lies Kumara Dewi; Eka Ubaya Taruna Rauf (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Human Resources is a very essential element in the development of an organization or institution. Quality Human Resources will create quality organizations or institutions as well. Sang Bumi Ruwa Jurai University as an educational organization is also committed to developing human resources, in this case lecturers, to become qualified and competitive lecturers. The research aims to determine the development of human resources in improving the performance of lecturers and to find out the factors that encourage and inhibit lecturers' performance. The research was conducted on Saburai University lecturers. The research method used descriptive qualitative methods. The results of the study concluded that several efforts have been made for the development of Human Resources in improving Lecturer Performance, namely: 1) Providing opportunities for lecturers to take doctoral studies with scholarship programs both from foundations and from the government (LPDP), 2 ) Providing opportunities for lecturers to participate in various kinds of training, both those that have been programmed by their respective units as well as training activities that are invited from other parties, such as improving the quality of scientific writing, there is a Scientific Writing Assistance program from LLDikti, PEKERTI training, in collaboration with Lampung University, training on proposals making to obtain competitive grants, online journaling training and research methodology training. Barriers 1) There is no special program or priority program for the development of professional competence of lecturers, 2) There is no ongoing training program to support the activities of the Tri Dharma of Higher Education, namely for the implementation of education and teaching, for research and for community service, 3) There is still a lack of the ability and motivation of lecturers to improve their qualifications.